1992
DOI: 10.1007/bf00160462
|View full text |Cite
|
Sign up to set email alerts
|

The boll weevil vitellogenin gene: Nucleotide sequence, structure, and evolutionary relationship to nematode and vertebrate vitellogenin genes

Abstract: Boll weevil (Anthonomus grandis) eggs contain two yolk proteins, YP47 and YP160. Using anti-YP160 antiserum as probe, a partial-length complementary DNA (cDNA) was isolated from a lambda gt11 adult female cDNA library. A second partial-length cDNA was isolated from a lambda gt10 adult female cDNA library by differential screening with male vs. female cDNAs. Northern blot analysis showed that each cloned cDNA hybridized to a 6-kb female-specific transcript. These cDNAs were used to probe a genomic library, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 53 publications
(61 reference statements)
5
60
0
Order By: Relevance
“…Several analyses based on the conserved N-terminal regions of Vtgs revealed a closer relationship between the Vtgs from nematodes and insects compared with Vtgs from vertebrates (61,68). In contrast, other analyses suggest a closer relationship between the Vtgs from nematodes and vertebrates compared with Vtgs from insects (4,(71)(72)(73). The difference between the two groups of analyses may be explained by the fact that the Vtg trees were unrooted (73), rooted using an insect Vtg rather than a non-Vtg LLTP (72), or interpreted without taking the included apoB outgroup into account (4,73).…”
Section: Three Families Of Lltpsmentioning
confidence: 99%
“…Several analyses based on the conserved N-terminal regions of Vtgs revealed a closer relationship between the Vtgs from nematodes and insects compared with Vtgs from vertebrates (61,68). In contrast, other analyses suggest a closer relationship between the Vtgs from nematodes and vertebrates compared with Vtgs from insects (4,(71)(72)(73). The difference between the two groups of analyses may be explained by the fact that the Vtg trees were unrooted (73), rooted using an insect Vtg rather than a non-Vtg LLTP (72), or interpreted without taking the included apoB outgroup into account (4,73).…”
Section: Three Families Of Lltpsmentioning
confidence: 99%
“…These probes can be used to screen genomic libraries, with clones that contain big fragments of genomic DNA (i.e., 15-45 kb), to select those with the gene of interest, including control regions, regulatory elements, and introns. This strategy has been followed to fully characterise the diapause protein 1 of Leptinotarsa decemlineata (Koopmanschap et al, 1995) or the vitellogenin gene in Anthonomus grandis (Trewitt et al, 1992).…”
Section: Genomic Pools Libraries and Cdna Sequencingmentioning
confidence: 99%
“…The gene for vitellogenin has been studied in two weevil species, including A. grandis and the white pine weevil, Pissodes strobi (Trewitt et al, 1992;Leal et al, 1997). The vitellogenin beetle gene shows a high degree of conservation from nematodes to vertebrates and insects, even with regard to the exon-intron structure (Trewitt et al, 1992). The interest in this gene and its regulation, apart from being relevant to understand the molecular mechanisms of oogenesis, also roots in the fact that its expression seems affected by certain host characteristics.…”
Section: Genes Involved In the Energetic Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…The Vgs have been studied extensively in various animals from vertebrates to invertebrates (Nardelli et al, 1987;Chen et al, 1997;Tufail and Takeda, 2008) and some highly conserved structures related with biological functions of Vgs Trewitt et al, 1992;Chen et al, 1997;Lee et al, 2000), such as polyserine tracts, DGXR motif, subtilisin-like endoproteases site (R/KXXR/K) and GL/ICG motif (Taborsky, 1991;Dhadialla et al, 1992;Mayadas and Wagner, 1992;Giorgi et al, 1999;Tufail et al, 2005) are found. The insect Vgs are synthesized mainly in fat body and have the tissue-, stage-and sex-specific characteristics Sappington et al, 2002).…”
Section: Introductionmentioning
confidence: 99%